THE CT AND MRI FINDINGS IN STAGING OF URINARY BLADDER CARCINOMA IN CORRELATION WITH HISTOPATH.FINDINGS (World Bulletin of Public Health, 2022)
More than 12 million new cases of cancer occur annually worldwide. Of those 5.4 million occur in developed countries and 6.7 million in developing countries. Urinary bladder cancer ranks ninth in worldwide cancer incidence. It is the seventh most common malignancy in men and seventeenth in women